The implementation of employee assistance programme at Makhado Municipality in Limpopo Province - Mugari, Elias Levers (University of Limpopo, 2011)
The provision of Employee Assistance Programme in a working environment such as a municipality is very crucial. In order to determine the effectiveness of the implementation of the programme to justify its existence to the outside world and to assess the impact of its fulfilment to its objectives, evaluation is therefore necessary. The aim of this research study was to ascertain the implementation of the EAP at the Makhado Municipality in Vhembe District with special focus on the employees’ awareness of the programme, its utilization and also the programme adequacy. A qualitative approach was used in this study. Forty two (42) employees of various ranks or level’s in the municipality were randomly selected to participate in the study, and they were from all the four main centres of the municipality i.e. Makhado, Waterval, Dzanani and Vuwani. Summary of the Main Findings A high percentage (81%) of the employees knew of the existence of an EAP within the municipality, and meetings appeared to be the main awareness strategy. − The attitudes of employees towards the EAP were positive, this state of affairs points to the usefulness of the EAP service. − The EAP provided by the Municipality was viewed as accessible by the majority of employees. − The utilization rate of the EAP in the Municipality was very low as only 17% of respondents indicated that they had utilized the service before. − The majority of referrals were conducted by supervisors while only 9.1% were self referral. The majority of respondents did not answer the question implying various reason/s and could also mean lack or poor knowledge and information about referrals within the programme. (iv Implementation of the EAP at Makhado Municipality in Limpopo Province − The majority of employees did not respond to the question on whether they were satisfied with the EAP within the municipality, and that could translate into low knowledge and information about the programme. − The majority of employees were generally happy with the current location of EAP in the municipality. − The majority of employees viewed EAP as confidential and the level of trust in the EAP staff was high. − The majority of employees were not aware of the EAP policy and never participated in its formulation. − The majority of employees felt that EAP services were useful, and this means that provision of proper information might encourage employees to use the service. − Most employees suggested that frequent dissemination of information to employees through meetings, workshops and other regular contact sessions could enhance the EAP in the municipality. Recommendations The following recommendations with regard to the employees’ familiarity with the EAP are important: o That more awareness sessions be conducted with all employees, especially those at regions unit so that adequate information is cascaded to all employees of the municipality. o The awareness sessions should be conducted at least quarterly involving all regions, and the EAP Advisory Committee should meet at least bi-monthly to discuss aspects to improve and enhance EAP services in the municipality. o It is also recommended that additional qualified EAP personnel, with at least minimum qualifications in Social Work and, or Social Psychology, or any relevant (v Implementation of the EAP at Makhado Municipality in Limpopo Province qualifications and experience in EAP be appointed to run the programme on full-time basis. o That evaluation of the programme implementation should be conducted using the participatory strategies such as suggestion boxes, arranging focus groups and bench-marking with other institutions. The recommendation to allow employees opportunities to submit suggestions, in-puts and give feedback regarding the programme will no doubt assist in the improvement and promotion of the programme. o The Makhado Municipality should utilize different marketing strategies as recommended by EAP literature, such as the following: i. The use of promotional material such as brochures, leaflets, and posters that are user-friendly and in languages understandable by all employees of the municipality. ii. Outreach programmes: The EAP unit needs to regularly visit all the regional offices of the municipality in order to intensify information sharing to employees about the EAP. These can also include decentralising EAP workshops to the periphery offices in order to reach the employees who are far away from the head office in Louis Trichardt. The above-mentioned could serve as effective strategies in promoting and maximising the visibility of the EAP, and may close the gap on information not reaching all employees in the municipality thereby increasing its penetration rate.
Thesis ( M.Dev.) --University of Limpopo, 2011
Keywords: Employee Assistance Programme; 331.2550968257; Employee assistance programs; Employee fringe benefits; Municipal officials and employees -- South Africa